The Upper Notec and Goplo Lake sailing trail and place of water tourism - Rafał Gotowski; Krzysztof Parzych; Wiktoria Karczewska; Aleksandra Gotowska (Kazimierz Wielki University, 2018)
The Upper Notec as sailing trail were built jfl 1870-1878 aim of supply of the Bydgoszcz Canal in water. The Upper Notec made possible sailing among Goplo Lake and Bydgoszcz. The article presents the Upper Notec from Pakosc to Kruszwica and Goplo Lake as water trail, touristic advantage of Goplo Lake, and restriction of sailing on water trail, with today used predominantly in tourism.